Mapping Insularity: a Visual History of Islands in Medieval and Early Modern Worlds - Wittmann, Kevin Rodríguez, (Brill Research Perspectives in Humanities and Social Sciences., 2025)
What lies behind an island? Is an island just a piece of land surrounded by water? Or is it from a cultural, symbolic and even geographical perspective much more than that? Considering the symbolic nature of islands as a longue durée and through the analysis of maps, texts and historical accounts, this book explores how the depiction of insularity encodes specific meanings and analytical levels which shed light on medieval and modern worldviews.